APPLICATION OF IMPORTANCE PERFORMANCE ANALYSIS (IPA) AND CUSTOMER SATISFACTION INDEX (CSI) METHOD TO ANALYZE INDONESIAN NAVAL 2ND FLEET COMMAND MATERIEL SERVICE PERFORMANCE - Juni Heri Budianto; Abdul Rahman; Sutrisno Sutrisno (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
ABSTRACT Indonesian naval 2nd fleet command materiel service (Dismatbek) is responsible for fulfilling all Indonesian warship (KRI) spare parts material, distribution of individual equipment and distribution of oil and lubricant fuel needs for KRI and other user. In order to increase the services, a research is needed to analyze the performance of service attributes provided by Indonesian naval 2nd fleet command materiel service. By using the Importance Performance Analysis (IPA) method, will be known the service attribute position in quadran analysis , and to know the satisfaction level of the user, it can use the Customer Satisfaction Index (CSI) method, the result get a value of 71.4%, even if it is in the category of satisfied (66% - 80%) there are still 4 attributes from 12 service attributes located in the first quadrant wich means it is need to be fixed immediately so the level of satisfaction level will be better. Keywords: Service Attributes, Importance Performance Analysis, Quadran Analysis, Customer Satisfaction Index